First Study of the Prosthesis Indication Deafnesses in Mureș County - Gabriel Lostun (Acta Medica Marisiensis, 2015)
Objective: The aim of this study was to asses the frequency of the deafness pathology in the Ear, Nose and Throath Clinic of the Emergency County Hospital in Tîrgu Mureș and two other private institutions that have an ear linked profile, with a special interest on those with indication for prosthesis. This is a pilot study, being conceived as a part of a larger one used to measure the number of possible cochlear implant recipients nationwide.